2021
DOI: 10.11591/ijphs.v10i3.20870
|View full text |Cite
|
Sign up to set email alerts
|

Work readiness during COVID-19 among taxibike online drivers in Samarinda, Indonesia

Abstract: COVID-19 caused a pandemic around the world, including in Indonesia. This greatly affected the informal business sector, such as online taxibike drivers. The success of this program to control the spread of COVID-19 is greatly influenced by knowledge, attitudes, and actions in the community. The purpose of this study was to identify behavioral factors during the pandemic. An online survey was conducted with 100 online taxibike drivers using a structured questionnaire and Google Forms. Data were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These cases were mainly contracted at community places. Likewise, studies by Setyowati et al [31] found that the impact of COVID-19 on the informal business sector, including online motorcycle taxi drivers, affects efforts to control the spread of the disease. Kshirsagar et al [32] highlight the pandemic's impact on workplace learning and businesses, while Furuse et al [33] identified 22 probable primary case-patients for the clusters, most of whom were 20-39 years of age and presymptomatic or asymptomatic at virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…These cases were mainly contracted at community places. Likewise, studies by Setyowati et al [31] found that the impact of COVID-19 on the informal business sector, including online motorcycle taxi drivers, affects efforts to control the spread of the disease. Kshirsagar et al [32] highlight the pandemic's impact on workplace learning and businesses, while Furuse et al [33] identified 22 probable primary case-patients for the clusters, most of whom were 20-39 years of age and presymptomatic or asymptomatic at virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Drivers who slept less than that time will feel less refreshed and are more at risk of experiencing fatigue at work Quamilla and Martiana (2022). The amount of sleep duration is needed so that it can be useful for optimizing the performance of online motorcycle taxi drivers (Setyowati et al, 2021). Several factors could influence sleep duration, including the length of work, which causes online taxi bike drivers to need more sleep (Manuel and Wirawan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The fast-paced advancement of information technology has left a considerable imprint on every individual within society, extending its influence even to healthcare [1]. The COVID-19 pandemic that has spread worldwide has affected various aspects of life, including social structure, economics, and education [2], [3]. The use of technology is an alternative to continue carrying out life activities according to established health protocols to prevent the chain of transmission of the coronavirus.…”
Section: Introductionmentioning
confidence: 99%